2010
DOI: 10.1371/journal.pone.0012413
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Constitutive Promoters in Human ES cells

Abstract: BackgroundConstitutive promoters that ensure sustained and high level gene expression are basic research tools that have a wide range of applications, including studies of human embryology and drug discovery in human embryonic stem cells (hESCs). Numerous cellular/viral promoters that ensure sustained gene expression in various cell types have been identified but systematic comparison of their activities in hESCs is still lacking.Methodology/Principal FindingsWe have quantitatively compared promoter activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 40 publications
6
105
0
Order By: Relevance
“…We first established a plasmid vector with an optimal promoter for expression in human stem cells. In a previous study using lentivirus reporters expressed in hESCs, EF1α was identified as producing the most robust and stable gene expression during differentiation programs (Norrman et al, 2010). We found this to be true as well, when comparing GFP reporter expression in H7 cells transiently transfected with plasmids driven by CAG (chick beta-actin enhancer), CMV, and EF1α.…”
Section: Objective 1: Evaluate the Combination Of Genetic And Neurotrsupporting
confidence: 52%
“…We first established a plasmid vector with an optimal promoter for expression in human stem cells. In a previous study using lentivirus reporters expressed in hESCs, EF1α was identified as producing the most robust and stable gene expression during differentiation programs (Norrman et al, 2010). We found this to be true as well, when comparing GFP reporter expression in H7 cells transiently transfected with plasmids driven by CAG (chick beta-actin enhancer), CMV, and EF1α.…”
Section: Objective 1: Evaluate the Combination Of Genetic And Neurotrsupporting
confidence: 52%
“…They usually achieve high levels of gene expression in most cell types. 26 However, these promoters may be transcriptional silenced due to extensive methylation. Previous studies have also shown that elongation factor 1α (EF1α) and constitutive cytomegalovirus (CMV) enhancer/chicken β-actin promoter (CAGG promoters are consistently strong in all mammalian cell types tested, whereas the CMV promoter is the most variable, being very strong in some cell types and rather weak in others.…”
Section: Suicide Gene Strategiesmentioning
confidence: 99%
“…27 Norrman et al found that ACTB (human β-actin promoter), EF1α and PGK promoters showed stable activities during longterm culture of undifferentiated hESCs. 26 Therefore, a promoter that can mediate stable, highly active suicide gene expression in human PSCs should be chosen for the clinical translation of hiPSCs in order to control wayward pluripotent stem cells and their progenies in vivo.…”
Section: Suicide Gene Strategiesmentioning
confidence: 99%
“…For this reason, the selection of an appropriate promoter should be determined on a case-by-case basis. Recent studies have systematically compared many of the commonly used promoters in a variety of cell types (Norrman et al, 2010;Qin et al, 2010) (Figure 4). These types of references are an excellent source of information when designing constructs with specific expression needs.…”
Section: Regulatory Elements Involved In Transcriptionmentioning
confidence: 99%